The Influence of the False Eyelash Sewing Technique in Party Makeup on the Self-Identity Formation of Makeup Students - A. Nur Maida; Izmi Burhanuddin; Annisa Putri; Novia Restu Windayani (Information Technology Education Journal, 2025)
Look beautiful with false eyelashes is part of facial appearance. This research is quantitative descriptive which aims to find out 1. Characteristics of false eyelashes with sewing techniques in party makeup by Makeup students. 2. Factors influencing false eyelashes with sewing techniques with self-identity formation. 3. The effect of false eyelashes with sewing techniques on students' self-identity. The research uses quantitative descriptive with case study approach on 5 models and 30 respondents through observation, interviews, documentation and score sheets. Data analysis uses frequency distribution, percentage, mean, and standard deviation. Results showed (1) using 2-3 thin false eyelashes with sewing technique takes 15 seconds for natural, voluminous appearance in four models, while one model required 30 minutes due to sensitive eyes. The technique produces proportional appearance and lasts in various temperatures; (2) influencing factors include internal factors (willingness, interest, motivation, student effort) contributing 60%, and external factors (environment, social media, criticism) contributing 40% (3) false eyelashes with sewing technique influences students' self-identity through self-confidence (33%), professional attitude (29%), social recognition (21%), and personality (17%). Usage levels per respondents' scores: low category (16-17) 5 people (16.67%), medium category (18-19) 10 people (33.33%), high category (20) 15 people (50%). Statistical analysis shows minimum score 16, maximum 20, mean 18.83, standard deviation 1.29. The use of false eyelashes with sewing techniques received positive response and became important for visual identity and professional makeup students.